Unveiling the nature of cathodoluminescence from photon statistics - Sotatsu Yanagimoto; Naoki Yamamoto; Tatsuro Yuge; Takumi Sannomiya; Keiichirou Akiba (Communications Physics)
Abstract Cathodoluminescence (CL), the emission of light induced by accelerated free electrons, has been extensively utilized in various applications, such as displays, streak cameras, and high-spatial-resolution analysis of optical materials, surpassing the diffraction limit of light. Despite its long history, the photon statistics of CL have only recently been examined, revealing unexpectedly large bunching of photons. Here we find that this peculiar photon bunching contains information of intervening excitation processes before the photon emission, which can be extracted from the photon statistics within each excitation event by a single free electron. Using this approach, we experimentally unveiled the statistical differences of coherent CL involving a single electromagnetic interaction process and incoherent CL involving multiple excitation processes. The developed formulation is universally applicable for particle generation processes in general to investigate the nature of cascade reactions.